Acculturative stress and eating disorder psychopathology: A meta-analysis. (January 2023) - Kalantzis, Maria A.; Chung Xiann Lim, Sam; Dauber, Aubrey K.; Studer-Perez, Emma I.; Silverman, Zachary J.; O'Brien, William H.
Abstract: The present meta-analysis aims to extend Doris and colleagues' (2015) systematic review and address the comprehensive, quantitative gap in the relation between acculturative stress and eating disorder psychopathology reported by studies in the past 20 years. A total of 14 eligible studies were included in our meta-analysis. Across all study samples, there were 2681 participants. The overall relation between eating disorder psychopathology and acculturative stress measurements was examined. Moderation analyses were run to investigate the substantial heterogeneity detected between studies. Results indicated a small effect size for the relationship between eating pathology behaviors and acculturative stress. These results provide insight for clinicians working with individuals who are experiencing acculturative stress, as well as highlight future research directions. Highlights: Acculturative stress (AS) is a risk factor for eating disorder psychopathology. Small effect size between AS and eating disorder psychopathology across studies. Most commonly used measurement for AS across studies was the SAFE. No significant moderation effects of BMI, time of publication, age, or sex.